Phenotypic and genetic features of a novel clinically isolated rough morphotype Candida auris - Tian, Sufei; Bing, Jian; Chu, Yunzhuo; Li, Hailong; Wang, Qihui; Cheng, Shitong; Chen, Jingjing; Shang, Hong (Frontiers in Microbiology, 2023)
Candida auris is a newly emerging pathogenic fungus of global concern and has been defined by the World Health Organization (WHO) as a member of the critical group of the most health-threatening fungi. This study reveals and reports for the first time that a rough morphotype C. auris strain causes urinary tract infections in non-intensive care unit (ICU) inpatients. Furthermore, we analyzed the phenotypic and genetic characteristics of C. auris possessing rough morphotype colonies compared to their smooth morphotype counterparts. The newly identified phenotypic variation of C. auris appears round, convex, dry, and burr-like with a rough texture. Scanning electron microscopy (SEM) shows that rough type C. auris has a rough and uneven colony surface with radial wrinkles and irregular spore arrangement. Cells of the rough morphotype C. auris naturally aggregate into clusters with tight connections in the liquid, and it seems that the cell division is incomplete. A genome-wide analysis of the rough type C. auris confirmed its genetic association with the smooth type of C. auris prevalent in China (Shenyang) two years ago; however, single nucleotide polymorphism (SNP) mutations of five genes (ACE2, IFF6, RER2, UTP20, and CaO19.5847) were identified more recently. RNA-seq revealed IFF2/HYR3, DAL5, PSA31, and SIT1 were notably up-regulated, while multiple cell wall-associated genes (ALS1, MNN1, PUL1, DSE1, SCW11, PGA38, RBE1, FGR41, BGLI, GIT3, CEP3, and SAP2) were consistently down-regulated in rough morphotype C. auris. This novel rough phenotypic variant of C. auris will provide a basis for further studies concerning the evolutionary characteristics of C. auris.